Performance of steel slag as replacement of natural aggregate in wearing course of flexible pavement - Ali, Zulfiqar (2014)
A byproduct obtained from steel industry known as steel slag, is reflecting as a construction material throughout the world. Mainly there are two types of steel slag, Basic Oxygen Furnace (BOF) and Electric Arc Furnace (EAF) obtained from steel industry. Steel slag is further processed to obtain different grades of aggregate to be used in pavement construction. Not all but most of the physical properties of steel slag are similar to the natural aggregate. This project was carried out to evaluate the performance of EAF steel slag aggregate in AC 14-wearing course mix. Where the conventional granite aggregate was replaced with steel slag. Five dense graded mix designs were incorporated with penetration grade 80/100 bitumen binder. The EAF steel slag was used to replace granite aggregate at percentage of 0, 25, 50, 75 and 100%. The same gradation as used for natural aggregate was followed for steel slag aggregate also, in accordance with Jabatan Kerja Raya (JKR) specification. Marshall mix design was used to obtain the optimum bitumen content (OBC) for test samples. The asphaltic concrete samples were examined through sand patch test to evaluate the surface texture depth of five different asphalt concrete mixes. The same mixes were also evaluated to find out the skid resistance of samples. The overall results of samples containing steel slag show productive results as compare to the conventional aggregates. These results confirm the potential of steel slag aggregate, and appreciate the use of EAF steel slag for the construction of green pavements by saving natural resources of aggregate.